Genome-wide identification and expression profiling of DnaJ gene family in Gossypium barbadense reveals candidate thermotolerance genes - Han, Ziling; Li, Chao; Li, ShuGuang; Xu, Jingchen; Li, Wenlong; Wang, Hemeng; Liu, Yiling; Wang, Yanqin (Frontiers in Plant Science, 2026)
IntroductionHeat stress is one of the primary abiotic stress factors affecting plant growth, seriously compromising crop quality and yield. The DnaJ gene family functions as a crucial component of molecular chaperones, playing a vital role in protein folding, unfolding, translocation, and degradation.ResultsIn this study, 109 GbDnaJ genes were identified and characterized in Gossypium barbadense, divided into five subfamilies based on the phylogeny analysis. Segmental duplication was identified as the primary driver for GbDnaJ family expansion, with the family underwent significant expansion and experiencing whole-genome duplication (WGD) events during the polyploidization process. The majority of duplicated gene pairs within Gossypium barbadense, as well as orthologous genes between related cotton species, were subjected to strong purifying selection. Cis-acting regulatory elements analysis revealed that the promoter regions of GbDnaJ genes are enriched with light-responsive, hormone-responsive and stress-responsive elements, and may be involved in cotton fiber development. Expression profiles demonstrated tissue-specific patterns for most GbDnaJ genes. Further investigation of 15 heat stress-responsive genes using RNA-seq data revealed divergent expression trends across tissues, with several genes showing strong stress-induced expression. These molecular patterns were closely associated with physiological changes, including decreased photosynthetic rate and increased activities of catalase and peroxidase.DiscussionThis study provides the first comprehensive analysis of the evolutionary and functional characteristics of the GbDnaJ gene family, offering theoretical insights and candidate gene resources for elucidating DnaJ-mediated thermotolerance mechanisms in Gossypium barbadense.